Thinner and better: (Ultra-)low grammage bacterial cellulose nanopaper-reinforced polylactide composite laminates - Hervy,M; Bock,F; Lee,KY (Composites Science and Technology, 2018)
One of the rate-limiting steps in the large-scale production of cellulose nanopaper-reinforced polymer composites is the time consuming dewatering step to produce the reinforcing cellulose nanopapers. In this work, we show that the dewatering time of bacterial cellulose (BC)-in-water suspension can be reduced by reducing the grammage of BC nanopaper to be produced. The influence of BC nanopaper grammage on the tensile properties of BC nanopaper-reinforced polylactide (PLLA) composites is also investigated in this work. BC nanopaper with grammages of 5, 10, 25 and 50gm−2 were produced and it was found that reducing the grammage of BC nanopaper from 50gm−2 to 5gm−2 led to a three-fold reduction in the dewatering time of BC-in-water suspension. The porosity of the BC nanopapers, however, increased with decreasing BC nanopaper grammage. While the tensile properties of BC nanopapers were found to decrease with decreasing BC nanopaper grammage, no significant difference in the reinforcing ability of BC nanopaper with different grammages for PLLA was observed. All PLLA composite laminates reinforced with BC nanopapers possessed similar tensile modulus of 10.5–11.8GPa and tensile strength of 95–111MPa, respectively, at a BC loading fraction =39–53vol.-%, independent of the grammage and tensile properties of the reinforcing BC nanopaper.